Les périurbains franciliens : vers de nouveaux comportements de mobilité ? - Martine Berger; Mireille Bouleau; Catherine Mangeney (EchoGéo)
Residents of periurban areas are often considered to be forced to travel long distances. The observation of recent trends in mobility in the outer suburbs and periurban fringe of Paris (based on censuses and transport surveys) highlights a stabilization of average distances and travel-time budgets of commuting trips. A growing tendency towards shorter shopping trips, greater diversity of these areas and their resources, and a clear relationship between local supply in terms of amenities and services, and household mobility strategies are revealed. Observations highlight the diversity of these periurban areas – particularly those located in the west of the Paris region – and also display a continuity in mobility patterns between the fringes and the periurban suburbs which are clearly distinguished from the urban core.